Islamic Education in Supporting De-radicalization: A Review of Islamic Education in Pondok Pesantren - Tiyas Nur Haryani; Muhammad Ikhsanul Amin; Nur Hidayatul Arifah; Arina Mardhiyana Husna (FITK UIN Walisongo, 2018)
This article present of the result of research about pondok pesantren (Islamic religious boarding school) education in confronting radicalism, focusing in researching the efforts of Pondok Pesantren Darusy Syuhadah in confronting radicalism. Collecting qualitative data through observation, documentation, and purposively sampled interviews. The result shows that pesantrens have a significant role in overcoming radicalism through its management of education model and curricula. Pondok Pesantren Darusy Syuhadah with Salaf education model build teaching and education to create generation of da’i (Islamic missionaries) and teachers of Islamic religion, so the curriculum prioritizes politeness and away from radicalism. AbstrakArtikel ini mempresentasikan hasil penelitian tentang pendidikan pondok pesantren dalam menghadapi radikalisme, memfokuskan pada upaya yang dilakukan pesantren Salaf di Pondok Pesantren Darusy Syuhadah dalam menghadapi radikalisme. Data kualitatif dikumpulkan melalui observasi, dokumentasi, dan wawancara purposive sampeling. Hasilnya menunjukkan bahwa pesantren memiliki peran yang signifikan dalam mengatasi radikalisme melalui pengelolaan model pendidikan dan kurikulumnya. Pondok Pesantren Darusy Syuhadah dengan model pendidikan Salaf membangun pengajaran dan pendidikan untuk menciptakan generasi da'i dan guru agama Islam, sehingga kurikulumnya mengutamakan kesantunan dan jauh dari radikalisme.